KOMITMEN KERJA, MOTIVASI KERJA DAN BUDAYA ORGANISASI TERHADAP KINERJA GURU MADRASAH - Tri Kamilatun Nahdiyah; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT Employee performance is a crucial aspect that can affect the overall performance of the organization. in this case, employee performance is influenced by determinant factors, which are also important to be considered by management. This study aims to analyze the influence between work motivation and organizational culture commitment to the performance of religious teachers at Al Ishlahiyah Islamic Boarding School in Malang Regency. The penetration method that is applied is quantitative with the type of data, namely primary data taken by questionnaire. The data analysis method applied is Multiple Linear Regression in the SPSS program. Decision making on hypothesis testing uses a real level (α) of 0.05 (5%). The results of the analysis show a significance value (p-value) <0.05 on all variables, both in the F test (simultaneous) and t (partial) test. Thus, it can be concluded that the work commitment of work motivation and organizational culture has a significant influence on the performance of religious teachers at the Al Ishlahiyah Islamic Boarding School in Malang Regency. Keywords: Performance, Commitment, Motivation, Organizational culture